Influence of continents and lithospheric plates on the shape of d" layer and the spatial distribution of mantle plumes - Trubitsyn V.P.; Evseev M.N.; Trubitsyn A.P. (Федеральное государственное бюджетное учреждение науки Геофизический центр Российской академии наук, 2015)
The regularities of the global intraplate volcanism of the Earth are explained by the mantle plumes originating at the heads and margins of two piles of dense material of the hot and relatively heavy $D''$~layer at the base of the mantle. Due to thermal blanket effect under a supercontinent the overheated region with ascending flows arises in the mantle. These flows distort the $D''$~layer and produce the thermochemical piles in the lowermost mantle under the supercontinent. It is supposed that the pile under Africa originated at the time of existence of Pangea, while the pile under the Pacific Ocean originated at the time of existence of Rodinia. As Africa succeeds to Pangea, the pile under Africa exists until now. But it stays unclear why the pile under the Pacific Ocean exists up to now despite supercontinent Rodinia has been broken-up a long time ago. The numerical models of thermochemical convection in the whole mantle with spherical geometry which include the heavy $D''$~layer allow to clear up effects of supercontinents and lithospheric plates on deformations of the $D''$~layer by mantle flows and formation of the thermochemical piles.
Keywords: CONVECTION; LOWER MANTLE; D" LAYER; PLUMES; PLUMES